OPEC : policy implications for the United States (New York, 1980)
This book is based on work done at Charles River Associates (CRA) as part of a larger research project for the Experimental Technology Incentives programm (ETIP) of the National Bureau of Standards, U.S. Department of commerce, That project dealt with alternative public policies (including technological change) to minimize the impact of raw material supply disruption. This book would not have written without not have been written without substantial contributions from others. While we cannot thank all of them by name we wish to mention the following Gregory C. Tassey, Technical Monitor at ETIP.
Keywords: Organisation of petroleum exporting countries